Modulation of cortical and subcortical brain areas at low and high exercise intensities. Issue 2 (16th August 2019) - Fontes, Eduardo Bodnariuc; Bortolotti, Henrique; Grandjean da Costa, Kell; Machado de Campos, Brunno; Castanho, Gabriela K; Hohl, Rodrigo; Noakes, Timothy; Min, Li Li
Abstract : Introduction: The brain plays a key role in the perceptual regulation of exercise, yet neuroimaging techniques have only demonstrated superficial brain areas responses during exercise, and little is known about the modulation of the deeper brain areas at different intensities. Objectives/methods: Using a specially designed functional MRI (fMRI) cycling ergometer, we have determined the sequence in which the cortical and subcortical brain regions are modulated at low and high ratings perceived exertion (RPE) during an incremental exercise protocol. Results: Additional to the activation of the classical motor control regions (motor, somatosensory, premotor and supplementary motor cortices and cerebellum), we found the activation of the regions associated with autonomic regulation (ie, insular cortex) (ie, positive blood-oxygen-level-dependent (BOLD) signal) during exercise. Also, we showed reduced activation (negative BOLD signal) of cognitive-related areas (prefrontal cortex), an effect that increased during exercise at a higher perceived intensity (RPE 13–17 on Borg Scale). The motor cortex remained active throughout the exercise protocol whereas the cerebellum was activated only at low intensity (RPE 6–12), not at high intensity (RPE 13–17). Conclusions: These findings describe the sequence in which different brain areas become activated or deactivated during exercise of increasing intensity, including subcortical areas measured with fMRI analysis.